2002
DOI: 10.1152/ajpheart.00238.2001
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic assessment of LV hypertrophy and function in aortic-banded mice: necropsy validation

Abstract: .-We characterized the time course of the left ventricular (LV) geometric and functional changes after aortic banding, validated them by necropsy, and investigated the sensitivity of echocardiographic findings on LV hypertrophy. C57BL/6 mice were subjected to transverse aortic constriction (TAC) or sham operation; echocardiographic assessments were performed before or at 2, 4, 6, and 11 wk after surgery; and some of the mice were euthanized at the corresponding time points. There was a progressive increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
94
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(109 citation statements)
references
References 16 publications
14
94
0
Order By: Relevance
“…Figure 4 shows representative M-mode and 2D echocardiographic images of control, dKO, and tKO mice. The mean FS for control mice was 50.1%Ϯ5.0%, corresponding to data reported by several groups for conscious 38 and anesthetized 33,35,37 mice. There were clear defects in LV wall motion in dKO and tKO mice compared with controls (Table; Figure 4).…”
Section: Cardiac Structure and Functionsupporting
confidence: 81%
See 1 more Smart Citation
“…Figure 4 shows representative M-mode and 2D echocardiographic images of control, dKO, and tKO mice. The mean FS for control mice was 50.1%Ϯ5.0%, corresponding to data reported by several groups for conscious 38 and anesthetized 33,35,37 mice. There were clear defects in LV wall motion in dKO and tKO mice compared with controls (Table; Figure 4).…”
Section: Cardiac Structure and Functionsupporting
confidence: 81%
“…Echocardiography was used to assess cardiac function and hypertrophy [33][34][35][36][37] in lightly anesthetized (pentobarbital; 25 mg/kg IP) dKO and tKO mice and their SR-BI-positive littermate controls (Table). No significant differences between RAG2(Ϫ/Ϫ) and RAG2(ϩ/ϩ) control mice were observed; therefore, all controls were pooled.…”
Section: Cardiac Structure and Functionmentioning
confidence: 99%
“…Short axis echocardiography images were obtained by Sonos 5500 (Agilent Technologies, Palo Alto, CA, USA) workstation and 12-MHz transducer. Left ventricular end-diastolic (EDD) and endsystolic dimension (ESD) measurements were manually digitized, using parasternal short axis view 33 and were in millimeter units. Percentage FS was calculated as % FS ¼ (EDD-ESD)/ (EDD) Â 100.…”
Section: Echocardiographymentioning
confidence: 99%
“…We have previously demonstrated that pulmonary edema is a reliable index of cardiac function in this model (10,18,19). Compared with that in sham mice, the lung/body weight ratio (LW/BW) was increased by 93% in TAC mice, whereas there was only a 17% increase of the LW/BW in the TAC +atorvas-tatin group (Fig.…”
Section: Atorvastatin Slows the Onset Of Heart Failurementioning
confidence: 84%
“…Male C57BL/6J mice (7-8 weeks old and weighing 20-24 g) were anesthetized with a mixture of intraperitoneal xylazine (5 mg/kg) and ketamine (100 mg/kg). Transverse aortic constriction (TAC) was performed to induce cardiac hypertrophy and heart failure, as described previously (9,10).…”
Section: Transverse Aortic Constriction Model and Experimental Protocolmentioning
confidence: 99%